Modeling of the end milling process for aluminum alloy AA6061T6 using hss tool - Najiha, M. S.; M. M., Rahman; A. R., Yusoff (Penerbit Universiti Malaysia Pahang, 2013)
This study is focused to determine the optimum operating parameters for the end milling process of AA6061T6 under wet cooling conditions. A central composite design of response surface methodology is used to develop an effective analytical model for surface roughness. The primary cutting parameters, namely, speed, feed rate and depth of cut, are considered in this study. Surface roughness is measured using a perthometer. The adequacy of the model is tested using ANOVA at 95% confidence level. Significant parameters are identified in terms of the cutting parameters. The obtained results show that the most significant parameters for the machining of the mentioned alloy are feed rate and depth of cut. The resultant model is then tested for optimization using a genetic algorithm.